2013
DOI: 10.1016/j.bbamem.2013.01.021
|View full text |Cite
|
Sign up to set email alerts
|

The electrical response of bilayers to the bee venom toxin melittin: Evidence for transient bilayer permeabilization

Abstract: Melittin is a 26-residue bee venom peptide that folds into amphipathic α-helix and causes membrane permeabilization via a mechanism that is still disputed. While an equilibrium transmembrane pore model has been a central part of the mechanistic dialogue for decades, there is growing evidence that a transmembrane pore is not required for melittin’s activity. In part, the controversy is due to limited experimental tools to probe the bilayer’s response to melittin. Electrochemical impedance spectroscopy (EIS) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
100
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 66 publications
(97 reference statements)
1
100
2
Order By: Relevance
“…57 Wiedman et al reported a similar phenomenon for melittin. 58 High concentrations of melittin induced a rapid burst of leakage of vesicle-entrapped fluorescent dyes.…”
Section: Melittinmentioning
confidence: 99%
See 1 more Smart Citation
“…57 Wiedman et al reported a similar phenomenon for melittin. 58 High concentrations of melittin induced a rapid burst of leakage of vesicle-entrapped fluorescent dyes.…”
Section: Melittinmentioning
confidence: 99%
“…58 Here, we use coarse-grained MARTINI model simulations to elucidate the behaviour of ruptured pores in the presence of melittin peptides. The simulated systems are some ten times larger than the CHARMM 29 all-atom simulations presented above, albeit with a more crude representation of molecular interactions.…”
Section: Melittinmentioning
confidence: 99%
“…A melittin concentration of P: L=1:100 was shown to induce an initial and rapid leakage of vesicle-entrapped fluorescent dyes, which then slowed to zero within ~10 minutes [85]. This result suggests a dynamic evolution of the membrane pore from an initially large size upon rupture, shrinking within minutes to a final state of either no pore, or one with a radius too small to allow passage of the dye.…”
mentioning
confidence: 75%
“…verified that melittin can generate pores by suddenly rupturing the lipid membrane [85]. A melittin concentration of P: L=1:100 was shown to induce an initial and rapid leakage of vesicle-entrapped fluorescent dyes, which then slowed to zero within ~10 minutes [85].…”
mentioning
confidence: 99%
See 1 more Smart Citation